One Site Is Enough: A Theoretical Investigation of Iron‐Catalyzed Dehydrogenation of Formic Acid. Issue 36 (31st July 2013) - Sánchez‐de‐Armas, Rocío; Xue, Liqin; Ahlquist, Mårten S. G.
<x xml:space="preserve">Abstract</x> Dehydrogenation of HCO2H: The reaction mechanism for the dehydrogenation of formic acid catalyzed by a highly active and selective iron complex (see figure) has been studied by DFT. The most favorable pathway shows the hydride in Fe–H complexes acting as a spectator ligand throughout the catalytic cycle. This result opens up the Fe complex for modification in order to achieve more efficient and selective catalysts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>